A Comparative Analysis of Ash Leaf-Colonizing Bacterial Communities Identifies Putative Antagonists of Hymenoscyphus fraxineus - Ulrich, Kristina; Becker, Regina; Behrendt, Undine; Kube, Michael; Ulrich, Andreas (Frontiers in Microbiology, 2020)
In the last few years, the alarming spread of Hymenoscyphus fraxineus, the causal agent of ash dieback, has resulted in a substantial threat to native ash stands in central and northern Europe. Since leaves and leaf petioles are the primary infection sites, phyllosphere microorganisms are presumed to interact with the pathogen and are discussed as a source of biocontrol agents. We studied compound leaves from susceptible and visible infection-free trees in four ash stands with a high likelihood of infection to assess a possible variation in the bacterial microbiota, depending on the health status of the trees. The bacterial community was analysed by performing culture-independent 16S rRNA gene amplicon sequencing and through the isolation and taxonomic classification of 2,589 isolates using matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). The bacterial community structure did not show significant differences. However, a set of amplicon sequence variants (ASVs) and MALDI groups belonging to Luteimonas, Aureimonas, Pseudomonas, Bacillus and Paenibacillus were distinctly increased in tolerant trees, which may be associated with the ability of the tree to resist the pathogen. The most obvious differences were observed for Luteimonas, a genus that is also exclusively present in the healthy core microbiome. In a first in vitro screen of antagonists, approximately 11% of total isolates suppressed the growth of H. fraxineus, but a statistical test with two different H. fraxineus strains only confirmed the antagonistic activity of 8% of these isolates. The antagonistic isolates were assigned to Bacillus velezensis, Pantoea vagans and Pseudomonas caspiana. Overall, our study provides a set of isolates or phylogenetic groups that might be involved in the process that prevents the penetration and spread of H. fraxineus. In the next step, in planta experiments are required with a longer period of exposure to H. fraxineus to evaluate effective isolates or consortia of isolates acting through direct antagonism or competition or indirectly by inducing resistance.